INTEGRATED FERTILIZATION FORMULATION: EFFECT OF GOAT MANURE AND PEARL NPK ON BIOMASS AND YIELD OF STRING BEANS - Della Howu Howu Zendrato; Helmin Parida Zebua; Dian Agung Sanora Laia; Putra Hidayat Telaumbanua; Natalia Kristiani Lase; Yoel Melsaro Larosa; Yarman Gulo; Ridho Victory Nazara (Universitas Nias Raya, 2025)
This study aims to evaluate the effect of goat manure and Mutiara NPK inorganic fertilizer on the vegetative growth, biomass, and yield of long bean (Vigna sinensis L.). The research was conducted using a factorial Randomized Group Design (RAK) consisting of two main factors. The first factor was the dose of goat manure with three levels: J1 (2 kg/plot), J2 (3 kg/plot), and J3 (4 kg/plot). The second factor was the application of NPK Mutiara fertilizer with four levels: P0 (control/no treatment), P1 (100 kg/ha or 24 g/plot), P2 (150 kg/ha or 36 g/plot), and P3 (200 kg/ha or 49 g/plot). Each experimental unit consisted of a uniform number of long bean plants to ensure reliable observations. The results indicated that both goat manure and NPK fertilizer significantly influenced vegetative growth parameters, including plant height, leaf number, and stem diameter, as well as yield components such as pod number, pod length, and total biomass. Furthermore, there was a significant interaction between goat manure and NPK application, where the optimal combination resulted in the highest biomass accumulation and pod yield. Specifically, the combination of the highest goat manure dose (J3) and moderate NPK dose (P2) provided the most favorable effect on long bean growth and productivity. These findings suggest that integrating organic and inorganic fertilizers can optimize nutrient availability, support sustainable crop production, and improve long bean yields. The study provides practical guidance for farmers seeking environmentally friendly fertilization strategies to enhance legume crop performance, while promoting soil fertility and sustainable agricultural practices.